Online Marketing of Herbal Medicines and Supplements (Case Study of Farah Shop, Banjarmasin) - Herliani, Erna; Salim, Yeffriansjah; Suharto, Imam; Bolkiah, Muhammad Hassanal; Mukhlis, Iwan Fitriady (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The business of selling medicines and herbal supplements at Farah Shop was pioneered in mid-2017 by Farah Putriana as the official distributor for several brands such as HDI, DXN, Herbalife, and so on. Products sold include cough medicine, slimming medicine, honey, and so on. Farah's shop is located at Jalan Sultan Adam, Taekwondo complex Permai line III no. 7 Surgi Mufti Village, North Banjarmasin with telephone number 081254545594. The management of recording the purchase and sale of drugs and herbal supplements uses a semi-computer system by recording on a spreadsheet application, some business problems at Farah's shop such as the slow preparation of profit reports from the sale of medicinal and herbal supplement products, difficulties in obtaining final inventory reports of medicinal and herbal supplements, marketing of medicinal and herbal supplement products is still limited because prospective buyers must come in person or ask product questions to the admin using the Whatsup application, with With the rapid development of the internet at this time, the owner of Farah Shop considers it necessary to make better use of this technology by creating an online application where prospective buyers can view and choose the medicine or herbal supplement that they will buy directly. This will increase sales from the Farah Shop business. Another problem is that making reports on the total sales and purchases of medicines and herbal supplements which are carried out every month is constrained by time and effort due to the absence of a good computer system. Difficulties in seeing the final stock of drugs or supplements so that orders from buyers are often not fulfilled, research will make applications using MySQL and PHP databases with a general description of providing online sales services, which can serve buyers who come directly to Farah's shop or who will buy directly via the internet online. The application made can store buying and selling data of drugs and herbal supplements in the database. The application can quickly generate reports on the remaining stock of medicines and herbal supplements, as well as generate reports on the purchase and sale of medicines and herbal supplements at the Farah Banjarmasin Shop which can be viewed daily, weekly and monthly